Clinical Efficacy of Crizotinib as the First-Line Therapy of Advanced Non-Small-Cell Lung Carcinoma with ROS-1 Rearrangement: A Systematic Review - Muhamad Rizqy Fadhillah; Jamal Zaini (Indonesian Journal of Cancer, 2023)
Background: Crizotinib is a drug designed to treat advanced NSCLC with ROS-1 rearrangement. Nevertheless, no reviews have assessed available studies to determine the efficacy and safety of first-line crizotinib against advanced NSCLC with ROS-1 rearrangement.Methods: PubMed, Cochrane Library, EBSCOHost, and ScienceDirect, were searched, filtered by inclusion and exclusion criteria, and read the full text. The researchers summarized and extracted efficacy as the primary outcome, including patients’ best response (complete response, partial response, stable disease, progressive disease, disease control rate, and objective response rate) and prognosis (overall survival rate and progression-free survival rate). Safety was also extracted as the secondary outcome.Results: Out of 91 articles electronically searched, four observational studies were included, extracted, and summarized descriptively. After full-text reading, entire studies were included. Across studies, the median PFS of the first line crizotinib varied from 14.9 months, 23.0 months, and 18.4 months with the median OS being 60 days to “Not Reach.” The patients’ best responses were similar among the studies. However, two out of four studies did not report the adverse event outcome. This study concluded that first-line crizotinib was safe.Conclusions: This systematic review suggests the potency of the first line of crizotinib therapy in advanced NSCLC patients. Regarding the current limitation of included studies, further higher quality with subsequent research in this scope is needed.